2017
DOI: 10.3389/fimmu.2017.01392
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Peripheral Tolerance in Ongoing Autoimmune Inflammation Requires Interleukin 27 Signaling in Dendritic Cells

Abstract: Peripheral tolerance to autoantigens is induced via suppression of self-reactive lymphocytes, stimulation of tolerogenic dendritic cells (DCs) and regulatory T (Treg) cells. Interleukin (IL)-27 induces tolerogenic DCs and Treg cells; however, it is not known whether IL-27 is important for tolerance induction. We immunized wild-type (WT) and IL-27 receptor (WSX-1) knockout mice with MOG 35–55 for induction of experimental autoimmune encephalomyelitis and intravenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 54 publications
0
35
0
Order By: Relevance
“…Tsoumarkidou et al also found that tolerogenic CD1c + DCs regulate development of T regs via IL-27/IL-10 inducible co-stimulatory ligands ( 27 ). Rostami et al have published data showing that the induction of peripheral tolerance is dependent on IL-27-mediated signal transduction pathway in DCs ( 28 ). These data suggest that regulatory mechanisms of IL-27 in the immune system are extremely complex and that IL-27 may play a dual role in equilibrium between autoimmunity and immune tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Tsoumarkidou et al also found that tolerogenic CD1c + DCs regulate development of T regs via IL-27/IL-10 inducible co-stimulatory ligands ( 27 ). Rostami et al have published data showing that the induction of peripheral tolerance is dependent on IL-27-mediated signal transduction pathway in DCs ( 28 ). These data suggest that regulatory mechanisms of IL-27 in the immune system are extremely complex and that IL-27 may play a dual role in equilibrium between autoimmunity and immune tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…STAT1 −/− , STAT3 −/− , and WT BMDCs were generated according to a previously described protocol (3). Briefly, BM cells were seeded at 2 × 10 6 cells/mL in Petri dish in complete IMDM supplemented with 100 ng/mL of recombinant mouse Flt-3 (R&D Systems, Minneapolis, MN, USA).…”
Section: Generation Of Bmdcsmentioning
confidence: 99%
“…We and others have reported that i.v. delivery of auto-Ag in mice with EAE induces expression of PD-L1 by APCs (2,3). Given the importance of PD-1 and its ligands in immune tolerance, we investigated their role in i.v.…”
Section: Intravenous Tolerance Induction In Experimental Autoimmune Ementioning
confidence: 99%
See 2 more Smart Citations